Skills Demands in the Technology Industry: Perceptions of Students and Graduates in Computing - Otemaier, Rafaela; Albuquerque, Regina; Hernandes, Vinicius; Reinehr, Sheila; Malucelli, Andreia (Anais do Workshop sobre Educação em Computação (WEI); 2025: Anais do XXXIII Workshop sobre Educação em Computação, 2025)
The growing demand for IT professionals has revealed a gap between the skills acquired by graduates and the needs of the technology industry, especially in terms of soft skills. This study identifies the hard and soft skills most valued by technology companies and explores how students and graduates perceive these demands. A survey with 251 students, 561 graduates, and the analysis of 135 job advertisements were conducted. Results show that companies prioritize analytical skills and English fluency, which students often overlook, while graduates’ perceptions align more with industry needs due to their experience. These findings highlight the need for universities to adapt curricula to better prepare graduates and bridge the skills gap, enhancing their employability.